The Role Of Managerial Ownership In Moderating The Effect Of Capital Structure, Profitability, And Dividend Payments On Company Value In The Infrastructure Sector Listed On The Indonesian Stock Exchange For The Period 2019–2024 - Dewi Rosmiati; Herry Achmad Buchory (UNIVED Press, 2026)
This study aims to analyze the effect of capital structure, profitability, and dividend policy on firm value with managerial ownership as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange during the period 2019–2024. Firm value is an important indicator that reflects performance and investor perceptions of a company's future prospects. Capital structure, profitability, and dividend policy are suspected to be the main factors affecting company value, while managerial ownership plays a role in aligning the interests of management and shareholders.This study uses a quantitative approach with a causality method. The data used is secondary data in the form of annual financial reports of infrastructure sector companies. The sampling technique was carried out using purposive sampling. Data analysis was performed using panel data regression and Moderated Regression Analysis (MRA) to test the role of moderating variables. The results show that capital structure and profitability have a significant effect on company value, while dividend policy does not have a significant effect on company value. Managerial ownership can moderate the effect of capital structure and profitability on company value, but does not moderate the effect of dividend policy on company value. These findings indicate that managerial ownership plays an important role in strengthening the influence of financial performance on increasing company value.This study is expected to contribute to the development of corporate finance studies and serve as a consideration for investors and management in making financial decisions.